Pajak Penghasilan Bagi Pelaku Bisnis Konten Kreator Di Platform Youtube - niluh, martiniasih; Saravistha, Deli Bunga; Kadek Dedy Suryana (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
The massive development of internet technology has significantly impacted the consumption patterns of information and economic activities of society, including in Indonesia. YouTube platform as a medium for sharing content and a source of income for content creators through the Google AdSense monetization program. However, the emergence of this form of digital income poses new challenges in the taxation system, particularly regarding the clarity of tax jurisdiction, tax compliance, and the classification of income types. This research aims to analyze the regulation of income tax (PPh) obligations for YouTubers in Indonesia and identify the factors affecting the effectiveness of the implementation of these regulations. In the legal context, the imposition of income tax (PPh) on digital content creators needs to consider the principles of legal certainty and fiscal justice, especially when facing the cross-border and technology-based characteristics of the digital economy. The main issues faced include the complexity of digital transactions, differences in policies between countries, and low legal literacy among creative industry players. This research shows that although the government has issued several regulations, their implementation still faces obstacles, both in terms of supervision and taxpayer compliance and the incompatibility of the conventional tax system with digital economy practices. Therefore, adaptive tax system innovations, public education, and cross-sector collaboration are needed to ensure the sustainability of state revenue and protection for digital economy actors.